The Role of Financial Literacy in Mediating the Influence of BSI Mitraguna on the Growth of MSMEs in Aceh - Yeni Irawan; Diana Diana; Heri Fajri; Mariana Mariana; M. Yazid AR; Zahriatul Aini (Bulletin of Community Engagement, 2026)
This study investigates the influence of BSI Mitraguna financing on the development of micro, small, and medium enterprises (MSMEs) in Aceh, with particular attention to the role of financial literacy. Using a quantitative explanatory research design, the study focuses on active BSI Mitraguna financing recipients in Aceh. Respondents were selected based on specific criteria, including a minimum duration of financing engagement and ongoing MSME operations. Data were gathered through a structured questionnaire using a Likert scale and analyzed using the Structural Equation Modeling--Partial Least Squares (SEM-PLS) method with SmartPLS software. The results reveal that BSI Mitraguna plays a significant role in fostering MSME growth. It not only provides financial capital but also contributes to improving the financial literacy of MSME actors. Furthermore, financial literacy serves as a crucial intermediary, enhancing the effectiveness of financing in driving business development. These findings suggest that microfinance programs are more impactful when integrated with financial education tailored to the specific needs of local entrepreneurs. Ultimately, this study contributes to the growing body of knowledge on Islamic microfinance by demonstrating that the synergy between financing and financial literacy is essential for sustainable MSME development. It also provides practical implications for policymakers and financial institutions to design integrated financing models that not only support capital access but also strengthen entrepreneurial capacity, thereby enhancing long-term economic resilience and inclusive growth